A Patient-Based Needs Assessment for Living Well with Parkinson Disease: Implementation via Nominal Group Technique - Galit Kleiner-Fisman; Pearl Gryfe; Gary Naglie (Parkinson's Disease)
Background. Parkinson’s disease (PD) is a neurodegenerative condition with complex subtleties, making it challenging for physicians to fully inform their patients. Given that approximately 50% of Americans access the Internet for health information, the development of a multimedia, web-based application emphasizing targeted needs of people with Parkinson’s disease (PwP) has the potential to change patient’s lives. Objectives. To determine what information PwP perceive could enhance their quality of life. Methods. Group sessions utilizing nominal group technique (NGT) were conducted. Participants were asked “what information do you want to know about that would help you live well with PD?” Silent generation of ideas preceded discussion followed by anonymous ranking of items. A “summary score” (sum of rank × frequency) was calculated. Results. 36 individual items were collapsed into 9 categories. Coping with emotions, changing relationships, and social implications of PD were ranked as most important. Financial supports and skills for self-advocacy were also highly ranked. Conclusions. Qualitative research methodology was utilized to determine the unmet needs of PwP. Results of this survey will inform the development of a patient-oriented, online resource, the goal will be to provide information and strategies to improve symptom management, reduce disability and address all relevant concerns important to those affected by PD.